2006
DOI: 10.1007/s00439-006-0166-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation at the growth hormone (GH1) and growth hormone receptor (GHR) loci as a risk factor for hypertension and stroke

Abstract: An increased prevalence of both hypertension and cerebrovascular stroke is apparent in growth hormone (GH) deficiency whilst hypertension is a frequent complication in acromegaly. This has suggested a possible link between GH, stature and arterial function. Since the risk of both hypertension and stroke also appears to be inversely correlated with adult height, we have instigated an exploratory study to assess whether inter-individual variation in the genes encoding human growth hormone (GH1) and the GH recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 71 publications
(75 reference statements)
3
24
0
Order By: Relevance
“…The extended DNA fragments were spotted onto a 384-element silicon chip (SpectroCHIP, Sequenom), and then analyzed by a Bruker Biflex III MALDI-TOF Spectro-READER mass spectrometer (Sequenom). Genotyping of d3-GHR was done according to the method developed by Pantel et al (11) with modifications (12,13). For a given sample, we separately amplified full-length GHR isoforms and exon 3-deleted isoforms by two different PCRs using primer pairs G1:G3 and G1:G2, respectively.…”
Section: Patientsmentioning
confidence: 99%
“…The extended DNA fragments were spotted onto a 384-element silicon chip (SpectroCHIP, Sequenom), and then analyzed by a Bruker Biflex III MALDI-TOF Spectro-READER mass spectrometer (Sequenom). Genotyping of d3-GHR was done according to the method developed by Pantel et al (11) with modifications (12,13). For a given sample, we separately amplified full-length GHR isoforms and exon 3-deleted isoforms by two different PCRs using primer pairs G1:G3 and G1:G2, respectively.…”
Section: Patientsmentioning
confidence: 99%
“…A C182R substitution has been reported in a patient with hypertension in a study that also found an inverse correlation between adult height and central hypertension [19]. Unfortunately, the height of the patient carrying the C182R mutation was not reported.…”
Section: Clinical Significancementioning
confidence: 99%
“…Gigante B et al [52] reported that F2R genetic [53], including Npr1 and Npr3. Another of the candidate genes, growth hormone receptor (GHR), has been linked to hypertension in two independent studies [19,54]. In "The Québec Family Study", a study of genome-wide linkage analysis for systolic and diastolic blood pressure, Rice et al [55] found an association between polymorphisms of corticotrophin releasing hormone gene (CRH) and hypertension.…”
Section: Candidate Genes In Different Qtl On the Same Chromosome Are mentioning
confidence: 99%